Influence of physical culture and sport on the indicators of physical development in the schoolchildren (Environment & Health, 2017)
Physical activity is a leading factor in the forming of physical development and other indicators of children's health, physical culture and sports are defined as its main manifestations.Objective. We studied the influence of physical training and sport on the indicators of physical development of the schoolchildren.Materials and methods.We performed the anthropometric examinations of body length, weight, and chest circumference for the assessment of physical development of 1399 students aged 13-17 years. Assessment of the data was carried out by gender-age regression scales and percentile method.Results and discussion. (31.45±1.24)% of the students at secondary schools were established not to do their morning exercises (physical training) and (38.46±1.30)% of them not to go in for sports connected with physical activity. The girls did their morning exercises regularly 2.2 times less and went in for sport 1.6 times less than the boys. Re-fusal of the regular physical exercises of the schoolchildren is a risk factor for a disharmony of their physical development formed mainly owing to the deficiency of chest circumference and body weight. Proposals for the improvement of physical development of the schoolchildren were developed.
Keywords: physical training and sport; physical development; schoolchildren